Removal of Dye Toxicity from an Aqueous Solution Using an Industrial Strain of Saccharomyces Cerevisiae (Meyen) - Dilarri, Guilherme [UNESP]; de Almeida, Érica Janaina Rodrigues [UNESP]; Pecora, Hengli Barbosa [UNESP]; Corso, Carlos Renato [UNESP] (Springer Nature, 2016)
The use of synthetic dyes is commonplace in many industries, and the effluent is often dumped into the environment with no prior treatment. The aim of the present study was to analyze the use of an industrial strain of Saccharomyces cerevisiae (Meyen) for the removal of the textile dye Acid Blue 161 from an aqueous solution. Kinetic, isotherm, and thermodynamic models were created to evaluate the biosorption mechanisms. Fourier transfer infrared (FT-IR) spectroscopy was used to characterize and identify possible binding sites. A toxicity test was also performed using Artemia salina to analyze the degree of toxicity of the dye following treatment. The kinetic results demonstrated the occurrence of intraparticle diffusion in the yeast cells as the controlling mechanism of the sorption process. Biosorption followed the Langmuir model, except at pH 8.50, when it fit the Freundlich model. The thermodynamic results demonstrate that the biosorption process is spontaneous and endothermic. The FT-IR analyses confirmed the occurrence of a chemical reaction in acid pH, but physical adsorption only occurred at pH 8.50. The toxicity test showed that the use of the yeast biomass led to the complete removal of toxicity from the dye solution, demonstrating the effectiveness of the biosorption process in the treatment of effluents contaminated with these compounds.
Keywords: Azo dyes; Bioremediation; Biosorption; Chemisorption; Toxicity test; Yeast